Employees Perception of Organizational Crises and Their Reactions to Them – A Norwegian Organizational Case Study - Sørensen, Jarle Løwe; Ranse, Jamie; Gray, Lesley; Khorram-Manesh, Amir; Goniewicz, Krzysztof; Hertelendy, Attila J. (Frontiers in Psychology, 2022)
Organizational sensemaking is crucial for resource planning and crisis management since facing complex strategic problems that exceed their capacity and ability, such as crises, forces organizations to engage in inter-organizational collaboration, which leads to obtaining individual and diverse perspectives to comprehend the issues and find solutions. This online qualitative survey study examines how Norwegian Sea Rescue Society employees perceived the concept of an organizational crisis and how they sensed their co-workers react to it. The scope was the ongoing COVID-19 pandemic, a global event affecting all countries and organizations and responding similarly globally. Data were collected during the Fall of 2020. The instrument of choice was the Internal Crisis Management and Crisis Communication survey (ICMCC). The results showed that the overall sample strongly believed in their organization's overall resilience level. However, a somewhat vague understanding of roles and responsibilities in a crisis where detected, together with some signs of informal communication, rumor spreading, misunderstanding, frustration, and insecurity. This study contributes to the academic field of organizational research, hence crisis management and sensemaking, and could be valuable to managers and decision-makers across sectors. Increased knowledge about how employees react to a crisis may help optimize internal crisis management planning and utilize robust mitigation and response strategies.